Pengukuran Produktivitas Personel dalam Penentuan Pemberian Insentif Karyawan di Perusahaan Pembangkit Listrik - Singgih, Moses Laksono; P, Bhakti Yudha (Jurnal Teknik Industri, 2007)
The measurement of productivity employer was crucial for the development of a organization and company. This was influenced for the company's working. One of the electricity's source company wanted to know how the achievements of employer's productivity are. This research is focused to maintaining department which concerned with three level division, they were specialist, supervisor, staff or technician crew. This research have done by using Will, can, May approach as the way to measure of the productivity's measurement. To conduct this research, it must be known the criterion of each elements, it used brainstorming with the company, and also the literature's reference. Another method which was used in this research is the priority each Will, Can, and May elements used Analytical Hierarchy Process (AHP) and fuzzy method to found single value which can form the productivity each employer as the achievement every elements of Will, can, and May. The result of this research showed that the productivity's achievement in middle and high scale from 43 employers who have measured their productivity. From the result of productivity's approach which have done was to know how are incentives which have got as the result of productivity each employer, and the result of incentive giving which have formulated gave the higher incentive's value than before. The result of giving more motivate the productivity of employer and the incentive's measurement didn't decrease the company from the benefit of allocation which is old incentive's giving and it is not look the stagnancy's nominal.